Rheological properties of fresh cement composites using compound rheology apparatus / Yong Chua Bon ... [et al.] - Bon, Yong Chua; Mohd Ali Al- Mattarneh, Hashem (Dr.); Ibrahim, Azmi (Dr.) (2007)
The rheology of concrete in general is important for the construction industry. Flow properties would affect the ease of placement, consolidation, durability, and strength. This study dealt with the development of new methods for determining flow properties of concrete. Tests were conducted on two mixtures using the first version of the probe penetration test. It was concluded that the relationships between the slump, Vebe, Compaction factor and the coefficient of X of the penetration probe were established. The coefficient of X can be used to estimate the slump and Vebe with good accuracy. It could determine the loss in slump with time. However, the rheological parameters could not be determined using the first version of the probe penetration test.